Double transplanting – A contingent strategy for rice cultivation in low-lying areas - S, Vijaya Kumar; Nayak, A. K.; Satapathy, B. S.; Munda, Sushmita; Tripathi, Rahul; Khanam, Rubina (Indian Farming, 2019)
Double transplanting is a traditional crop-establishment system in which rice seedlings are transplanted twice, first on secondary nursery, and then the main field. It is a contingent strategy in low -lying flood prone areas especially during Aman season rice. The need of double transplanting arises when the main field is not ready due to continuous stagnation of floodwater or due to delay in onset of monsoon. It is an indigenous technology developed by farmers to manage the risk of submergence. The single transplanted rice, the seedling height of young seedlings is not tall enough and has risk of submergence. Whereas, the height of double transplanted rice seedlings is tall and can withstand submergence relatively for longer time. In eastern India flood prone rice area occupies nearly 2.25 m ha most of which are rainfed. Uncertainty of monsoon makes sowing time of rice become unpredictable. Double transplanting, seems to provide solution under such situation. Sometimes this is used as a method for seedling multiplication under seedling scarce situation. This situation often arises when the established crop is damaged in field due to flash flood.